DO SOCIO-DEMOGRAPHIC CHARACTERISTICS AND FINANCIAL LITERACY MATTER FOR SELECTING ISLAMIC FINANCIAL PRODUCTS? - Salma Fadhilah Widityani; Taufik Faturohman; Raden Aswin Rahadi; Yulianti Yulianti (Bank Indonesia, 2020)
Indonesia is a promising market for the Islamic finance industry since most of the population is Muslim. However, the growth of Islamic finance in Indonesia is still low. Therefore, Islamic financial literacy needs to be improved in order to grow the Islamic finance industry significantly. The purpose of this study is to determine the factors that enhance Islamic financial literacy among college students in Indonesia. The development of validated constructs for Islamic financial literacy is important because conventional financial literacy might contain some elements that are not compatible with Islamic financial principles. This study also measures the level of Islamic financial literacy and its relationship with socio-demographic characteristics using multilinear regression. Furthermore, the relationship between Islamic financial literacy and the possession of Islamic financial products is observed by logistic regression. The determinant factors are perception, attitude and behaviour, and knowledge. The study found that type of educational institution, Islamic finance course experience, being educated to Master’s degree level, having one’s own income, and having an income above five million have a significant relationship with the Islamic financial literacy of college students. The factors that have a significant relationship with the possession of Islamic financial products are Islamic financial literacy, choice of major, Islamic finance course experience, and monthly income above five million. This research attempts to provide an Islamic financial literacy measurement through exploratory factor analysis. The development of a validated instrument for an Islamic financial literacy index and its determinant factors is our scientific and practical contribution to the literature on Islamic financial literacy in Indonesia.